Lives in limbo : undocumented and coming of age in America - Gonzales, Roberto G., 1969- (University of California Press, 2016)
"Over two million of the nation's eleven million undocumented immigrants have lived in the United States since childhood. Due to a broken immigration system, they grow up to uncertain futures. In Lives in Limbo, Roberto G. Gonzales introduces us to two groups: the college-goers, like Ricardo, whose good grades and strong network of community support propelled him into higher education, only to land in a factory job a few years after graduation, and the early-exiters, like Gabriel, who failed to make meaningful connections in high school and started navigating dead-end jobs, immigration checkpoints, and a world narrowly circumscribed by legal limitations. This ethnography asks why highly educated undocumented youth ultimately share similar work and life outcomes with their less-educated peers, even as higher education is touted as the path to integration and success in America. Gonzales bookends his study with discussions of how the prospect of immigration reform, especially the Deferred Action for Childhood Arrivals (DACA) program, could impact the lives of these young Americans"--